Optimization for the effects of Coconut Shell Activated Carbon Xerogel weight and temperature on the hydrogen sulphide adsorption using Response Surface Methodology - Mahdi, Hadi Hamdi; Mohammed Saleh, Ali; Alias, Azil Bahari; M. Ali, Obed; Wan Ab Karim Ghani, Wan Azlina; Shihab, Thaer Abdulwahhab; Mohammed Saleh, Noah; Yassin, Khalil Farhan (Praise Worthy Prize S.r.l, 2024)
One of Malaysia's major sources of biomass is the palm oil industry (POME). Due to its high disposal rate, the vast amount of biomass production has become known. As a result, many researchers have looked into the possibility of turning biomass into something useful like biochar. The biochar that was synthesized was used to absorb sour gases such as Carbon Dioxide and Hydrogen Sulphide. In this study, the main gas that was aimed to be absorbed is the Hydrogen Sulphide. Coconut kernel shell was used as the source of biochar in this study. Hydrogen Sulfide (H2S) is commonly known as a harmful substance to the environment and is considered one of the contributors to the high air pollution rate in various parts of the world. In this study, two main objectives are to optimize the Coconut Shell Activated Carbon Xerogel by using the Response Surface Methodology and to develop a Coconut Shell Activated Carbon Xerogel based on the optimized data from the Response Surface Methodology. There are much software used for applying Response Surface Methodology such as MINITAB and STATITISCA but for this study, the software that was chosen was Design Expert. Results show that the higher the adsorbent weight, the higher the removal efficiency at a medium temperature. In conclusion, 11.68 grams of adsorbent weight and 40 °C is the optimum condition for the adsorption process to occur for both 25 ppm and 50 ppm of H2S.